2017
DOI: 10.5194/npg-24-227-2017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of finite-time Lyapunov exponents on winter precipitation over the Iberian Peninsula

Abstract: Abstract. Seasonal forecasts have improved during the last decades, mostly due to an increase in understanding of the coupled ocean-atmosphere dynamics, and the development of models able to predict the atmosphere variability. Correlations between different teleconnection patterns and severe weather in different parts of the world are constantly evolving and changing. This paper evaluates the connection between winter precipitation over the Iberian Peninsula and the large-scale tropospheric mixing over the eas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The chaoticity of the pollutant advection can be studied by means of di erent quantities, such as the Lyapunov exponent describing the strength of the trajectory separation of initially nearby particles as well as the local mixing (see, e.g., Refs. [15][16][17][18][19][20][21] or the topological entropy [22][23][24] characterizing the rate of the exponential stretching of pollutant clouds in the atmospheric context and being closely related to the unpredictability of the spreading and the complexity of the structure of a pollutant cloud. 25,26 Due to the vertical component of air velocity and gravity, particles with nonzero mass (e.g., aerosol particles) carry out this complicated, chaotic motion for nite duration because they move downward on average.…”
Section: Introductionmentioning
confidence: 99%
“…The chaoticity of the pollutant advection can be studied by means of di erent quantities, such as the Lyapunov exponent describing the strength of the trajectory separation of initially nearby particles as well as the local mixing (see, e.g., Refs. [15][16][17][18][19][20][21] or the topological entropy [22][23][24] characterizing the rate of the exponential stretching of pollutant clouds in the atmospheric context and being closely related to the unpredictability of the spreading and the complexity of the structure of a pollutant cloud. 25,26 Due to the vertical component of air velocity and gravity, particles with nonzero mass (e.g., aerosol particles) carry out this complicated, chaotic motion for nite duration because they move downward on average.…”
Section: Introductionmentioning
confidence: 99%
“…FTLEs have been used to identify the presence of barriers to mixing in the atmosphere between the tropics and extratropics (Pierrehumbert and Yang, 1993) and to study the zonal stratospheric jet (Beron-Vera et al, 2008), jet streams (Tang et al, 2010), hurricanes (Rutherford et al, 2012), transient baroclinic eddies (von Hardenberg and Lunkeit, 2002), and the polar vortex (Koh and Legras, 2002). The predictability of the atmosphere for long periods of time has also been studied using FTLEs (Yoden and Nomura, 1993;Huber et al, 2001;Stohl, 2001;Garny et al, 2007;d'Ovidio et al, 2009;Ding et al, 2015;Garaboa-Paz et al, 2017). Moreover, the identification of ridges of maximum FTLEs (Shadden et al, 2005) allows for the detection of potential Lagrangian coherent structures or kinematic transport barriers that control flow mixing and folding over a period of time for the examples cited above.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding transport processes in simple kinematic models has helped to understand the essential ingredients of complex transport phenomena (Bower, 1991;Samelson, 1992;Samelson and Wiggins, 2006). In this Special Issue kinematic models are constructed by García-Garrido et al (2017), retaining fundamental features of complex fluid parcel evolution during the polar vortex breakdown in September 2002 and its previous stages. The authors showed that the breaking and splitting of the polar vortex are justified by the sudden growth of a planetary wave and the decay of the axisymmetric flow.…”
mentioning
confidence: 99%